District planning: concept, setting and state level applications - Hooja, Rakesh (Jaipur, 1986)
This book examines the rationale for decentralized planning and the suitability of the district as an appropriate planning unit. It then goes into three determinants which form the setting in which district planning has to be attempted-State level planning, the district level delivery system, and prospects of local level projectization.
Keywords: Public administration